From adolescence to awakening: portrayal of the ‘urban child’ in Charles Dickens’ novels - Tasnim, Nishat (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.